Inteligencia artificial y pensamiento real - Hernán, Francisco (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper focussses on the analysis of Hardy's point of view, «at bottom, all mathematicians think in the same way», and looks for its implications on teaching. Research on Artificial Intelligence provides some hints which suggest that a new approach to the relationship between concepts and processes.